Glycogen synthase kinases in model and crop plants – From negative regulators of brassinosteroid signaling to multifaceted hubs of various signaling pathways and modulators of plant reproduction and yield - Zolkiewicz, Karolina; Gruszka, Damian (Frontiers in Plant Science, 2022)
Glycogen Synthase Kinases, also known as SHAGGY-like Kinases (GSKs/SKs), are highly conserved serine/threonine protein kinases present both in animals and plants. Plant genomes contain multiple homologs of the GSK3 genes which participate in various biological processes. Plant GSKs/SKs, and their best known representative in Arabidopsis thaliana – Brassinosteroid Insentisive2 (BIN2/SK21) in particular, were first identified as components of the brassinosteroid (BR) signaling pathway. As phytohormones, BRs regulate a wide range of physiological processes in plants – from germination, cell division, elongation and differentiation to leaf senescence, and response to environmental stresses. The GSKs/SKs proteins belong to a group of several highly-conserved components of the BR signaling which evolved early during evolution of this molecular relay. However, recent reports indicated that the GSKs/SKs proteins are also implicated in signaling pathways of other phytohormones and stress-response processes. As a consequence, the GSKs/SKs proteins became hubs of various signaling pathways and modulators of plant development and reproduction. Thus, it is very important to understand molecular mechanisms regulating activity of the GSKs/SKs proteins, but also to get insights into role of the GSKs/SKs proteins in modulation of stability and activity of various substrate proteins which participate in the numerous signaling pathways. Although elucidation of these aspects is still in progress, this review presents a comprehensive and detailed description of these processes and their implications for regulation of development, stress response, and reproduction of model and crop species.